Մեծ եղեռնի ու Զմյուռնիայի հայ և հույն բնակչության զանգվածային կոտորածների համեմատական վերլուծություն - Մարուքյան, Արմեն Ց. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Առաջին աշխարհամարտում Օսմանյան կայսրության պարտությունը և իշխանությունից երիտթուրքերի հեռացումը որևէ կերպ չթեթևացրեց ոչ թուրք ժողովուրդների վիճակը, որոնք շարունակում էին ցեղասպանության և էթնիկ զտումների ենթարկվել: Հանցավոր քաղաքականության ցեղասպանական բնույթն արձանագրելու տեսակետից անհրաժեշտություն է առաջանում հայերի և հույների դեմ Առաջին աշխարհամարտի ընթացքում երիտթուրքերի կատարած ոճրագործությունները համեմատել պատերազմից հետո քեմալականների կատարած հանցագործությունների հետ՝ համադրելով դրանց փուլերը, ներգրավված ուժերը և մեթոդները: The defeat of the Ottoman Empire in World War I and the removal of the Young Turks from power in no way alleviated the plight of non-Turkish peoples, who continued to be subjected to genocide and ethnic cleansing. From the point of view of ascertaining the genocidal nature of the criminal policy pursued by the Turkish authorities, it becomes necessary to compare the genocidal acts committed by the Young Turks against Armenians and Greeks during the First World War with the mass massacres committed by the Kemalists after the war, by conducting a comparative analysis of the stages and methods, as well as those involved in these crimes of forces. A comparative analysis of these crimes leads to the conclusion that both during and after the First World War, immediately before the organization of the massacres of the Armenian and Greek populations, the Turkish regimes prepared the psychological and propaganda grounds for this, pursuing the goal of “justifying” and/or “substantiating necessity” of a planned criminal policy towards victim groups. The eviction and subsequent extermination of male victims from their places of residence, the subsequent massacres of defenseless women, children and the elderly, the burning of those who had taken refuge in churches, and many other similarities in the methods of the Young Turks and Kemalists indicate that these Turkish regimes in relation to non-Muslim and non-Turkish peoples carried out a uniﬁed policy of physical extermination and ethnic cleansing. The Kemalists consistently continued the genocidal policy of the Young Turks against the Armenian and Greek population, which is conﬁrmed by the massacre of Armenians in Cilicia in 1921, as well as the mass extermination of the Armenian and Greek population of Smyrna in 1922. Поражение Османской империи в Первой мировой войне и отстранение от власти младотурок никоим образом не облегчило положение нетурецких народов, которые продолжали подвергаться геноциду и этническим чисткам. С точки зрения констатации геноцидного характера проводимой турецкими властями преступной политики возникает необходимость сопоставления геноцидных действий, совершенных младотурками в отношении армян и греков в годы Первой мировой войны с массовыми погромами, совершенными уже кемалистами после войны, проведя сравнительный анализ этапов и методов, а также задействованных в этих преступлениях сил. Сравнительный анализ этих преступлений приводит к заключению, что как во время, так и после Первой мировой войны, непосредственно перед организацией массовых убийств армянского и греческого населения, турецкие режимы подготавливали психологическую и пропагандистскую почву для этого, преследуя цель “оправдать” и/ или “обосновать необходимость” спланированной преступной политики в отношении групп-жертв. Выселение и последующее истребление мужчин групп-жертв из их мест проживания, последующие после этого массовые убийства оставшихся беззащитными женщин, детей и стариков, сожжение укрывшихся в церквях и многие другие сходства в методах младотурок и кемалистов свидетельствуют о том, что эти турецкие режимы в отношении немусульманских и нетурецких народов осуществляли единую политику физического истребления и этнических чисток. Кемалисты последовательно продолжили геноцидную политику младотурок в отношении армянского и греческого населения, подтверждением чего являются массовая резня армян в Киликии в 1921 г., а также массовое истребление армянского и греческого населения Смирны в 1922 г.
Keywords: Օսմանյան կայսրություն; Հայոց ցեղասպանություն